The Capabilities of Paddy Rice and the Threshing Machines in Iraq - Alshatri, Shwan H. H. (Indonesian Journal of Agricultural Research, 2023)
This study aims to obtain rice from paddy rice and determine the capacity of the threshing machine that does such separation. The research question is how to convert the paddy rice into rice, then how to use the rice husk left the paddy rice, and its ground rice by-product while mixing the paddy rice of several people. Our research method is separating the rice, rice husk, and ground rice using several mathematical equations to find the value of paddy rice, rice husk, and ground rice. Finally, we will be able to distinguish between the amount of rice and the ground rice of each person simultaneously and know the capacity of the threshing machine that does the job. Some MATLAB code was utilized to validate the equations and produce the table.